Differential central regulatory mineralocorticoidreceptor systems for anxiety and depression – Could KCNJ5 be an interesting target for further investigations in major depression?. (December 2022) - Adolf, Christian; Murck, Harald; Sarkis, Anna-Lina; Schneider, Holger; Heinrich, Daniel A.; Williams, Tracy Ann; Reincke, Martin; Künzel, Heike
Abstract: The mineralocorticoid receptor (MR) is suggested to play a role in the pathophysiology of depression and anxiety. Main support comes from studies in patients with primary aldosteronism (PA) which suggested different central pathways for depression and anxiety mediated via the MR and gender differences. We investigated 118 patients with PA over 3 years using self-rating questionnaires for anxiety (GAD-7) and depression (PHQD) at baseline and once a year under specific treatment with adrenalectomy (ADX; n = 48) or a MR antagonist (MRA; n = 70). Genotyping for KCNJ5 mutation was performed in resected tumors. At baseline, patients treated by ADX or MRA had comparable scores for anxiety and depression. Females showed a better metabolic profile but higher scores of depression and anxiety, compared to males. Initiation of specific treatment for PA resulted in a better response in depressive symptoms after ADX and of anxiety under MRA treatment. However, GAD-7 and PHQD remained high in women over the three-year follow-up. KCNJ5 mutation, linked to co-secretion of hybrid steroids as 18-oxocortisol and 18-hydroxycortisol, was detected in 10 female and 2 male patients. They tended to have higher GAD and PHQD scores at baseline compared to patients without KNCJ5 mutation, but showed a significant better reduction in symptoms of anxiety during the 3-year follow up compared to patients without this mutation (all p < 0.05). These data support a differentiated regulation of depression and anxiety by the MR. Moreover, genetic mutations such as KCNJ5 could affect the pathophysiology of these disorders by impacting in adrenal steroidogenesis.